2022
DOI: 10.3390/fermentation8070335
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Electrical Parameters Using Sucrose in Tomato Waste

Abstract: The use of organic waste as fuel for energy generation will reduce the great environmental problems currently caused by the consumption of fossil sources, giving agribusiness companies a profitable way to use their waste. In this research, tomato waste with different percentages of sucrose (0-target, 5, 10, and 20%) was used in microbial fuel cells manufactured on a laboratory scale with zinc and copper electrodes, managing to generate maximum peaks of voltage and a current of 1.08 V and 6.67 mA in the cell wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…There are investigations that have managed to generate voltage greater than one volt in 100 mL cells for periods longer than 30 days, but there are still bottlenecks for its scaling. These are mainly the concentration of certain microorganisms present in the substrate for good performance, as well as the appropriate pH for its operation and the most suitable electrodes so that their maintenance is not too expensive [45,63,64]. On the other hand, MFCs have been used for the bioremediation of different types of toxic metals and the generation of bioelectricity at the same time, giving good indications that this technology will be a reality for society in the near future.…”
Section: Results and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…There are investigations that have managed to generate voltage greater than one volt in 100 mL cells for periods longer than 30 days, but there are still bottlenecks for its scaling. These are mainly the concentration of certain microorganisms present in the substrate for good performance, as well as the appropriate pH for its operation and the most suitable electrodes so that their maintenance is not too expensive [45,63,64]. On the other hand, MFCs have been used for the bioremediation of different types of toxic metals and the generation of bioelectricity at the same time, giving good indications that this technology will be a reality for society in the near future.…”
Section: Results and Analysismentioning
confidence: 99%
“…In this sense, as can be seen in Figure 7, the terms wastewater treatment, electricity, microbial fuel cells, electrolytic reduction, and oxygen are the most used by researchers for the preparation of manuscripts, although the authors with the most citations and most citations over the last thirty-two years are working with electrodes modified with nanostructures in wastewater treatment. The method of anaerobic digestion combined with chemical and thermochemical processes is the most used in water treatment; for example, in the extraction of lipids by thermochemistry [58][59][60][61][62][63]67,68]. Other types of combined technologies are those that include pyrolysis, liquefaction, and gasification for the production of fuels through wastewater [63,64].…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For the anodic and cathodic electrodes, copper (Cu) and zinc (Zn) 10 and 0.2 cm in diameter and thickness, respectively, were used. The Zn electrode was placed at one end of the tube with one side exposed to the environment and the other was exposed to the substrate used; while the anode electrode (Cu) was placed inside the MFCs, both electrodes were joined by an external circuit of Cu wire (0.25 cm in diameter) and a 100 Ω resistor, whose configuration was similar to that used in the work of Segundo et al (2022) [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…It was also observed that these values decreased over time, mainly due to the sedimentation of the organic components [ 27 ]. Likewise, tomato waste has been used as a substrate for the generation of electricity in single-chamber MFCs with zinc and copper electrodes, with voltage peaks close to 10.8 V and an internal resistance of 0.148541 ± 0.012361 KΩ being observed at the optimal acid pH for the operation of MFCs; this study is one of the most promising works to date [ 28 ]. It was observed that, in the investigations carried out, metallic electrodes are of great help in generating higher current and voltage values, while single-chamber MFCs obtain higher current and power density values [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%